Silica nanoparticles: the rising star in plant disease protection. (January 2022) - Kandhol, Nidhi; Singh, Vijay Pratap; Peralta-Videa, José; Corpas, Francisco J.; Tripathi, Durgesh Kumar
Abstract : When applied exogenously, silica (Si) can have a beneficial impact on plants under biotic stress conditions, as revealed by its recent application in the form of nanoparticles (SiO2 NPs) to induce pathogen resistance (El-Shetehy et al . ). This opens up a new window of research into combating the devastating effects of biotic stresses.